Supply Chain Sustainability Drivers: Identification and Multi-Criteria Assessment - Nikita Osintsev; Aleksandr Rakhmangulov (Logistics, 2025)
Background: Supply chains operate under the changing influences of multiple external and internal factors. Sustainable supply chain development requires an assessment of these factors, as well as drivers and barriers. Various sustainability assessment criteria, methods, and models based on the consideration of the influence of different factors are used depending on the type and structure of the supply chain. Methods: The combination of DEMATEL and CRADIS multi-criteria methods is applied to rank the efficiency of drivers for achieving sustainable development goals, both for the supply chain as a whole and for each of its structural elements. Results: This study proposes a system of drivers for sustainable supply chain development. The peculiarity of the used supply chain model is the universality of its structure, which ensures the realization by the structural elements of the chain of all known functional areas of logistics. A framework for sustainable supply chain drivers’ multi-criteria assessment based on the use of the original two-level system of drivers’ assessment criteria is developed. Conclusions: The results of the supply chain sustainability drivers’ ranking and the framework developed by the authors are intended to justify decisions on the green logistics methods and instrument selection.